Équations équilibrées la veille |
2 CH3CH2CH2CH3 + 13 O2 = 8 CO2 + 10 H2O
C7H8NO2 + KMnO4 + H2SO4 = C7H6O2NO2 + K2SO4 + MnSO4 + H2O =>
5 C7H8NO2 + 6 KMnO4 + 9 H2SO4 = 5 C7H6O2NO2 + 3 K2SO4 + 6 MnSO4 + 14 H2O
Sb2S3(s) + HCl = SbCl3 + H2S =>
Sb2S3(s) + 6 HCl = 2 SbCl3 + 3 H2S
AlBr3 + K2SO4 = KBr + Al2(SO4)3 =>
2 AlBr3 + 3 K2SO4 = 6 KBr + Al2(SO4)3
H2 + O2 = H2O =>
2 H2 + O2 = 2 H2O
KI + Na3PO4 = KPO4 + Na3I =>
KI + Na3PO4 = KPO4 + Na3I
C2H4O2 + SO4 = H2S + H2O + CO2 =>
5 C2H4O2 + 4 SO4 = 4 H2S + 6 H2O + 10 CO2
K20 = K =>
K20 = 20 K
Fe + HC1 = FeC1 + H2 =>
2 Fe + 2 HC1 = 2 FeC1 + H2
CU(OH)2 + HI = CUI2 + H2O =>
CU(OH)2 + 2 HI = CUI2 + 2 H2O
(NH4)2Fe(SO4)2 + KMnO4 + H2SO4 = Fe2(SO4)3 + MnSO4 + K2SO4 + (NH4)SO4 + H2O =>
10(NH4)2Fe(SO4)2 + 6 KMnO4 + 24 H2SO4 = 5 Fe2(SO4)3 + 6 MnSO4 + 3 K2SO4 + 20(NH4)SO4 + 24 H2O
CoCl2 + H2O = CoClOH + HCl =>
CoCl2 + H2O = CoClOH + HCl
CH3CHClCOOH + KHCO3 = CH3CHClCOOK + CO2 + H2O =>
CH3CHClCOOH + KHCO3 = CH3CHClCOOK + CO2 + H2O
NH4Cl + AgNO3 = AgCl + NH4NO3 =>
NH4Cl + AgNO3 = AgCl + NH4NO3
Mn4(CO4)3 + Ba(NO3)2 = Ba2(CO4) + Mn(NO3)3 =>
Mn4(CO4)3 + 6 Ba(NO3)2 = 3 Ba2(CO4) + 4 Mn(NO3)3
H2O = H2 + O2 =>
2 H2O = 2 H2 + O2
Fe2(SO4)3 + BaCl2 = BaSO4 + FeCl3 =>
Fe2(SO4)3 + 3 BaCl2 = 3 BaSO4 + 2 FeCl3
Li + MgI2 = LiI2 + Mg =>
Li + MgI2 = LiI2 + Mg
H2 + O2 = H2O =>
2 H2 + O2 = 2 H2O
As4O6 + I2 + H2O = As2O5 + HI =>
As4O6 + 4 I2 + 4 H2O = 2 As2O5 + 8 HI
NH4Cl + COSO4 = NH4SO4 + COCl =>
NH4Cl + COSO4 = NH4SO4 + COCl
Pd + Sc = Pd2Sc3 =>
2 Pd + 3 Sc = Pd2Sc3
C2H66 + O2 = C02 + H2O =>
2 C2H66 + 33 O2 = 2 C02 + 66 H2O
Mercury(II)Chloride + PotassiumSulfide = PotassiumChloride + Mercury(II)Sulfide =>
Mercury(II)Chloride + PotassiumSulfide = PotassiumChloride + Mercury(II)Sulfide
K3PO4 + Na2SO3 = Na2PO4 + K3SO3 =>
K3PO4 + Na2SO3 = Na2PO4 + K3SO3
Mercury(II)ChloridePotassiumSulfide = PotassiumChlorideMercury(II)Sulfide =>
Mercury(II)ChloridePotassiumSulfide = PotassiumChlorideMercury(II)Sulfide
Br2 + NaI = NaBr + I2 =>
Br2 + 2 NaI = 2 NaBr + I2
CH2(OH)2 + O2 = CO2 + H2O =>
CH2(OH)2 + O2 = CO2 + 2 H2O
Na + S = Na2S =>
2 Na + S = Na2S
Pb(ClO2)4 + Zn(SO4) = Pb(SO4)2 + Zn(ClO2)2 =>
Pb(ClO2)4 + 2 Zn(SO4) = Pb(SO4)2 + 2 Zn(ClO2)2